Application of Soil Conditioner, Nutrient Solution with Biofertilizer to Improve Soil Bio-chemical Properties on Red Chili Plant - Fitriatin, Betty Natalie; Putri, Envry Artanti Duidahayu; Simarmata, Tualar (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
Plant productivity is influenced by soil quality and availability of plant nutrients. Soil conditioner can improve soil quality by enhancing soil properties. Both macro and micronutrients can be fulfilled through application of nutrient solution containing macro and micronutrients and biofertilizer. This experiment was conducted from at experimental field of the Faculty of Agriculture, Universitas Padjadjaran to test the combination of soil conditioner, NPK fertilizer, nutrient solution (NS), and biofertilizer (BF) effects on soil biological and chemical properties and red chili growth. The experiment was designed using a Randomized Block Design with seven treatments and four replications. The treatments consisted of control, combination of NPK and NS with a dose of 0, 6, and 12 kg.ha-1 BF contained Azotobacter sp., Azospirillum sp., and Pseudomonas sp.. The doses used for a single application were 15 gplant-1 NPK and 300 mLplant-1 NS. Manure was applied to the control treatment and soil conditioner to the other treatments as a basic fertilizer at a dosage of 4 ton.ha-1. The results showed that the combination of soil conditioner, NPK fertilizer, nutrient solution, and biofertilizer had significant effects on soil biological properties and red chili growth, but didn’t show significant effect on soil chemical properties. The combination of soil conditioner + NPK + 12 kg.ha-1 BF increased soil fungal population (113,4 x 103 CFU.mL-1) and bacterial population (599,5 x 108 CFU.mL-1). Meanwhile, the combination of soil conditioner + NS + 6 kg.ha-1 BF increased plant height (60,48 cm).